Pattern of Thrombocytopenia In Pregnancy At Teaching Hospital Of Rahim Yar Khan, Pakistan - Ghafoor, Muhammad Bilal; Sarwar, Faiza; Durrani, Tahira Afzal; Azher, Zainab Quratulain; Jabeen, Saleha; Ali Khan, Muhammad Haris (Journal of Rawalpindi Medical College, 2023)
Background: Platelet count less than 150 × 109 / L is referred to as thrombocytopenia, which is the second common blood disorder in pregnancy after anemia. Although pregnancy is related with physiological variations in platelet count, however, several pathological conditions also cause thrombocytopenia showing significant impact on health of mother and her baby. The prevalence of thrombocytopenia during pregnancy is 7 to 11%. The physiological thrombocytopenia is multifactorial, related to hemodilution, increased platelet consumption and increased platelet aggregation. Objective: To determine the pattern of thrombocytopenia during third trimester of pregnancy in Rahim Yar Khan. Methodology: This cross-sectional study was carried out at Teaching Hospital of Rahim Yar Khan with effect from May 16, 2022 to September 30, 2022. Five hundred (500) pregnant females in their third trimester were the part of this study. All the study subjects were selected from the department of gynecology and obstetrics at Sheikh Zayed Hospital, Rahim Yar Khan which is a renowned teaching hospital of the region attached with Sheikh Zayed Medical College. Data collection was done on a pre-designed questionnaire. Sample of blood was taken in EDTA and Gel containing vacutainers by convenient sampling technique. Results: The frequency of thrombocytopenia during pregnancy was found 10.4%. Gestational thrombocytopenia was the most common type among thrombocytopenic pregnancies with frequency of 63.46% in comparison to pre-eclampsia 30.76%, HELLP Syndrome 3.80% and immune thrombocytopenic purpura 1.90%. The mean age of pregnant women was observed 27.53±5 years. There is no significant difference in number of thrombocytopenic patients from rural and urban areas (p=0.2). Conclusion: The frequency of thrombocytopenia during the third trimester of pregnancy is observed high, so the regular screening is necessary to avoid any adverse outcome. Specially the patients with Pre-eclampsia and HELLP syndrome should be monitored critically. Key words: Platelet Count, Thrombocytopenia in Pregnancy, Types of Thrombocytopenia, Pre-Eclampsia